Cognitive training in Parkinson's disease reduces cognitive decline in the long term. (22nd December 2014) - Petrelli, A.; Kaesberg, S.; Barbe, M. T.; Timmermann, L.; Rosen, J. B.; Fink, G. R.; Kessler, J.; Kalbe, E.
<x xml:space="preserve">Abstract</x> Background and purpose Patients with Parkinson's disease (PD) are at high risk for cognitive dysfunction. Non‐pharmacological interventions have attracted increasing interest for enhancing PD patients' cognitive functions. Methods One‐year follow‐up data (T2) of a randomized controlled trial evaluating two 6‐week cognitive trainings – a structured (NEUROvitalis, NV) and an unstructured (mentally fit, MF) program − compared with a waiting list control group (CG) in non‐demented PD patients (Hoehn and Yahr I–III) are presented. Forty‐seven PD patients were examined at T2. Effects on overall cognitive functions (Mini‐Mental State Examination and DemTect) were compared between all groups with repeated measurement analyses of variance. A combined score of the percentage change value from baseline (T0) to T2 was calculated to identify patients who retained or improved their cognitive state (responders). The risk of developing mild cognitive impairment (MCI) was analyzed. Results Significant time × treatment effects on overall cognitive functions were found for both training groups, each compared separately to the CG (DemTect, P < 0.05). Nine patients (56.3%) of the NV group, seven (41.2%) of the MF group and three (21.4%) of the CG were responders. Comparing NV to CG the odds ratio was 4.7 [95% confidence interval (0.8; 33.3)], and comparing MF to CG it was 2.6 [95% confidence interval (0.4; 17.4)]. MCI risk for patients without prior MCI was 40.0% in CG, 18.2% in MF and 18.2% in NV. The odds ratio was 3 comparing NV to CG, MF to CG. Discussion This study gives evidence that cognitive training may be effective to prevent cognitive decline and onset of MCI in PD patients.